Is classical mechanics based on Newton’s Laws or Eulers analytical equations? - Iro, H. (Condensed Matter Physics, 2005)
In an example I illustrate how my picture of physics is enriched due to my
frequent conversations with Reinhard Folk. The subject is: Who wrote down
the basic equations of motion of classical mechanics for the first time? (To
be sure, it was not Newton.) На одному прикладі я ілюструю, як збагатилась моя картина фізики завдяки частим розмовам з Райнгардом Фольком. Предметом є: хто вперше записав основні рівняння руху класичної механіки? (Без сумніву, це був не Ньютон).